Cultural evolution and the Biblical world - Luomanen, Petri (Vlog on hot spots and trends of recent research, 2019)
Prof. Petri Luomanen, Professor of New Testament and Early Christian Culture and Literature at the University of Helsinki, tells us about his current research project "Early Christianity in Cultural Evolution", funded by the Academy of Finland. We'll begin with a review of Prof. Luomanen's academic journey so far, learning how his doctoral and postdoctoral research eventually led him to analyse early Christianity in a social-scientific framework. We'll also meet Luomanen's research group and hear about the types of added value that the project on cultural evolution has given to the careers of the team members. Finally, Prof. Armin Geertz (Aarhus University), one of the advisory board members of Luomanen's project, shares his thoughts on the relevance of cultural evolutionary and bio-cultural approaches to the study of religion.